MEMBANGUN ETHICAL BEHAVIOR PEGAWAI BIDANG PENAGIHAN PAJAK (Studi Kasus Terhadap Juru Pungut di DISPENDA Kota Kupang) - Clarce Sarliana Maak (Universitas Nusa Cendana, 2019)
The implementation of the ethics in a state-owned institution becomes an attention that attract the public services sectors a specially in tax services sector. The flare of news in media about the fraudulence ethic as a result of tax evasion and the untehical information about the tax collector, built up a phenomenon and wrong assumptions about the tax notably the tax collector. Through the phenomenon,so the purposes of this research is to find out how far the department of local revenue of Kupang city that operate in the sector of public services especially the tax services, in responding and overcome ethical issues that happen in the office of the tax collector. This research uses the descriptive research with qualitative approach. The Data were collected through observation, interview, documents collecting and related report. The result of this research shows the tendency of ethical in office mostly determined by the impact of policy and leadership factors. For more, this research contribute with new propositions and could be tested in upcoming research. Keywords : Ethics, Policy, Ethics Violation, Work Performance, Individual and Organization.